2014
DOI: 10.1145/2661229.2661238
|View full text |Cite
|
Sign up to set email alerts
|

Topology-constrained synthesis of vector patterns

Abstract: Decorative patterns are observed in many forms of art, typically enriching the visual aspect of otherwise simple shapes. Such patterns are especially difficult to create, as they often exhibit intricate structural details and at the same time have to precisely match the size and shape of the underlying geometry. In the field of Computer Graphics, several approaches have been proposed to automatically synthesize a decorative pattern along a curve, from an example. This empowers non expert users with a simple br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In cases where the pattern is fairly regular and self-similar, Zhou et al [78] showed that a simpler dynamic programming technique can be used to synthesize patterns along curves. Later, Zhou et al [79] showed that decorative patterns can be synthesized with better controls over topology (e.g., number of holes and connected components), by first synthesizing the topology using a topological descriptor, and then synthesizing the pattern itself. This latter work also demonstrated design of 3D patterns, which we discuss next.…”
Section: Synthesis For Specialized Domainsmentioning
confidence: 99%
“…In cases where the pattern is fairly regular and self-similar, Zhou et al [78] showed that a simpler dynamic programming technique can be used to synthesize patterns along curves. Later, Zhou et al [79] showed that decorative patterns can be synthesized with better controls over topology (e.g., number of holes and connected components), by first synthesizing the topology using a topological descriptor, and then synthesizing the pattern itself. This latter work also demonstrated design of 3D patterns, which we discuss next.…”
Section: Synthesis For Specialized Domainsmentioning
confidence: 99%
“…To address this, a method for topology‐constrained pattern synthesis was proposed by Zhou et al [ZJL14]. Given a 2D exemplar, the method strives to tile it along a curve in a fabricable manner.…”
Section: Design For Appearancementioning
confidence: 99%
“…Several recent works consider the problem of decorating surfaces to turn them into printable objects, with the same purpose of customization for 3D printing. Zhou et al [2014] synthesize connected patterns along curves, and use their approach to model fabricable 3D objects. Dumas et al [2015] modify texture synthesis to account for structure and rigidity, and synthesize printable 3D patterns that cover a base surface.…”
Section: Previous Workmentioning
confidence: 99%